2013
DOI: 10.1177/1362361313509731
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ first concerns about toddlers with autism spectrum disorder: Effect of sibling status

Abstract: Symptoms of autism spectrum disorders may appear as early as 6 months, but parent concern, which can precipitate evaluation, often lags significantly. The presence of typical or atypical older siblings can change parents’ sensitivity to departures from typical development. This study investigated type and age of parent's first concerns in toddlers with autism spectrum disorder, prior to diagnosis. Participants had (1) at least one older sibling with ASD (Sibs-ASD); (2) only typically-developing older siblings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(86 citation statements)
references
References 34 publications
(75 reference statements)
5
71
0
4
Order By: Relevance
“…Retrospective reports of the age at which parents first became concerned indicate there may be some benefit of prior experience with an older diagnosed child in detecting early symptoms in later-born children, but the evidence is mixed. Herlihy et al (2013) found that while parents of firstborn children with ASD reported first becoming concerned around 16 months of age, parents of an older child with ASD reported first becoming concerned about the second child with ASD around 10 months of age. Conversely, Chawarska et al (2007) found no significant differences in the proportion of infants with diagnosed older siblings whose parents who reported first becoming concerned sometime in the first year of life, between 12 and 18 months, or later than 18 months.…”
Section: Clinical Utility Of Parent Concernsmentioning
confidence: 98%
See 2 more Smart Citations
“…Retrospective reports of the age at which parents first became concerned indicate there may be some benefit of prior experience with an older diagnosed child in detecting early symptoms in later-born children, but the evidence is mixed. Herlihy et al (2013) found that while parents of firstborn children with ASD reported first becoming concerned around 16 months of age, parents of an older child with ASD reported first becoming concerned about the second child with ASD around 10 months of age. Conversely, Chawarska et al (2007) found no significant differences in the proportion of infants with diagnosed older siblings whose parents who reported first becoming concerned sometime in the first year of life, between 12 and 18 months, or later than 18 months.…”
Section: Clinical Utility Of Parent Concernsmentioning
confidence: 98%
“…Despite these early symptoms, parents typically do not report concerns until the second year of life (Chawarska et al, 2007; De Giacomo & Fombonne, 1998; Herlihy et al, 2013; Hess & Landa, 2012; Veness et al, 2012). Retrospective reports of the age at which parents first became concerned indicate there may be some benefit of prior experience with an older diagnosed child in detecting early symptoms in later-born children, but the evidence is mixed.…”
Section: Clinical Utility Of Parent Concernsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, it was found that parents' accuracy in reporting their child's difficulties increases when they already have an older son-daughter, not necessarily affected (Herlihy et al, 2015). This evidence underlines the utility of these tools when used free from recalling biases to complete information acquired during well-child visits or during lab visits (i.e.…”
Section: Parental Reportsmentioning
confidence: 77%
“…Expressive language is often the first reported parental concern for children later diagnosed with ASD (De Giacomo & Fombonne, 1998;Herlihy, Knoch, Vibert, & Fein, 2015), and thus previous work has comprehensively explored the possible link between language and ASD (see Boucher, 2012 for a review). This previous work highlights that a range of language ability exists in the ASD population, in that there is a subset of children who present with intact structural language abilities (Grzadzinski, Huerta, & Lord, 2013); however, there is also a substantial number of individuals with ASD who also present with concomitant language difficulties (Buschmann et al, 2008;Luyster, Qiu, Lopez, & Lord, 2007;Rescorla, 2011;Rescorla & Safyer, 2013).…”
Section: Introductionmentioning
confidence: 99%